DNA damage in oral mucosa cells of patients with fixed orthodontic appliances. - Farzin Heravi; Mohammad Reza Abbaszadegan; Mohsen Merati; Nadia Hasanzadeh; Ezzat Dadkhah; Farzaneh Ahrari (Tehran University of Medical Sciences, 2013)
The release of toxic metal ions from orthodontic alloys has induced concerns regarding the biocompatibility of fixed appliances. This study investigated the genotoxic effect of metal appliances in a sample of patients undergoing fixed orthodontic treatment.The study included twenty-five healthy individuals requiring orthodontic therapy in both jaws. The patients were treated by stainless steel orthodontic brackets and nickel-titanium or stainless steel arch wires. The oral mucosa cells were gathered just before the appliance placement and 9 months later. The cells were centrifuged, fixed and dropped onto slides. After staining, the micronucleus (MN) assay was used to determine genome alteration. The data were analyzed by paired sample t-test.The mean micronuclei frequency in the buccal mucosa was 10.6 ± 5.7 per 1000 cells before the appliance placement and 9.2 ± 6.37 per 1000 cells 9 months later. No significant difference was found in the MN count before and 9 months after therapy (p=0.336).Under the conditions used in this study, application of fixed orthodontic appliances did not expose healthy individuals to increased risk of DNA damage in oral mucosa cells.